Acute Type B Dissection - Andre Ramdon (Radcliffe Medical Media, 2019)
Aortic dissections are catastrophic vascular emergencies, and early recognition and appropriate interventions can be crucial to survival. Research has changed the way aortic dissections are managed over the past two decades and will continue to contribute to the evolution of treatment modalities. Early treatment for uncomplicated type B dissections still remains controversial but certain characteristics may benefit from early intervention.